A review on the development of lead-free ferroelectric energy-storage ceramics and multilayer capacitors. Issue 47 (7th December 2020) - Zhang, Haibo; Wei, Tian; Zhang, Qi; Ma, Weigang; Fan, Pengyuan; Salamon, David; Zhang, Shan-Tao; Nan, Bo; Tan, Hua; Ye, Zuo-Guang
Abstract : Typical lead-free energy storage systems and their performances for dielectric and multilayer capacitors over the last decade. Abstract : Energy storage materials and their applications have attracted attention among both academic and industrial communities. Over the past few decades, extensive efforts have been put on the development of lead-free high-performance dielectric capacitors. In this review, we comprehensively summarize the research progress of lead-free dielectric ceramics for energy storage, including ferroelectric ceramics, composite ceramics, and multilayer capacitors. The results indicate that dielectric capacitors with both high energy density and high efficiency are feasible using the materials providing high breakdown electric field and a slim hysteresis loop. This article also lists the factors affecting the fabrication cost of dielectric capacitors, such as sintering temperature, raw material costs, and types of internal electrodes, to promote the industrial application of ceramic energy storage capacitors.